AUCLOS: Automatic Clothesline System with Led Infrared Based on Microcontroller Arduino Uno using Ambient Light and Steam Sensors - Elnino Profetika; Fadhiel Muhammad Alim; Muhammad Zaki Nur Nizam; Ray Wiratama (Jurnal Integrasi Sains dan Quran, 2022)
The development of technology is increasing very fast in this globalization era. But, the manual clothesline system that people use makes them raise it directly when the weather is uncertain sometimes distressed them. From that, we decided to make a prototype model of automatic clothesline built using Arduino Uno, that will simplify and shorten the time in lifting the clothesline for drying clothes even if the weather changes. In this study, the Arduino Uno microcontroller functioned as a data processor centers that will be obtained from the steam sensor to detect the rain water, ambient light sensor to detect the sunlight and also uses a servo to fold and unfold the roof. Testing results show that this prototype works well. When the device is turned on, the sensor will check the weather outside, whether it is rainy or sunny. When it is hot or sunny, the roof will keep folded. And if the weather gets dark or starts raining, the roof will be unfolded to cover the clothesline and turn on the infrared light automatically